Learning fraction with vacation: Integrating Musi Rawas tourism in designing learning trajectory on fraction - Sukasno; Zulkardi; Putri, Ratu Ilma Indra; Somakim (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Fraction learning has gained significant attention in mathematics education research, with a growing body of literature addressing the instructional challenges inherent in teaching fractions effectively. Establishing a solid conceptual foundation in fractions is critical to fostering broader mathematical proficiency, yet many students continue to struggle with core fractional concepts. This study addresses these issues by integrating a real-world context—Musi Rawas tourism—into fraction instruction, targeting pre-service elementary teachers enrolled in an elementary mathematics education program. Adopting a design research methodology, specifically a validation study, the study progresses through three structured phases: preliminary design, design experiments (encompassing pilot and teaching experiments), and retrospective analysis. Data collection involved teaching materials, observational checklists, and documentation to capture the instructional dynamics and learning outcomes. The study’s primary contribution is a localized instructional theory for teaching fractions within a tourism context, organized across five progressive learning activities: problem identification in the Gegas Water Lake tourism setting, contextual model development, model-based problem-solving, context-specific solution formulation, and abstraction of mathematical conclusions. This framework offers an innovative pedagogical approach, illustrating the potential for enhancing fraction learning through contextualized instruction in tourism, with detailed insights into the methodology and outcomes presented in the full study.